Conception of being elderly by Boca Maldita Gentlemen: a qualitative descriptive study - Maria Helena Lenardt; Karina S. de Almeida Hammerschmidt; Mariluci Hautsch Willig; Marcia Daniele Seima; Claudia Rodrigues de Araújo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
This is a qualitative descriptive study carried out with elderly members of the Confraternity of Boca Maldita Gentlemen, located on XV de Novembro Sidewalk - Curitiba downtown. The study aimed to investigate the members' conception of being elderly. Data were collected from November 2006 to January 2007 through semi structured interviews. Twelve interviews were conducted, which were analyzed through analysis of collective speech. The following main ideas emerged from qualitative analysis: 1. Elderly is the other; 2. Money is everything; 3. Sexuality is taboo. The participants of the study have a high education level, many with more than one degree and an income of 30 salaries. They demonstrated prejudice conceptions about what it is to be an elderly, similarly to elderly with low educational and social level.